Study of serum lipid profile in Plasmodium falciparum malaria - Dungdung, Ajith; Jalawadi, Vishwanath Malakappa; Yadav, Upendra Prasad (International Journal of Research in Medical Sciences, 2018)
Background: Malaria is a major public health problem in India with wide-ranging haematological and biochemical alterations. Plasmodium falciparum (P. falciparum) is one of four distinct species of the malaria parasite that afflict humans and pose a threat to public health. Under normal physiological conditions, liver ensures homeostasis of lipid and lipoprotein metabolism. Therefore, the aim of this study was to assess malaria infection and its association with lipid parameters changes. Hepatocellular damage often associated with severe and acute P. falciparum infections impairs these processes, leading to alteration in plasma lipid profile and lipoprotein patterns. An observation on the nature of dyslipidaemia in confirmed cases of P. falciparum malaria patients with reference to correlation if any that exists between malaria and lipid profile in these patients was performed. Methods: A case-control study was carried out on clinically and laboratory confirmed P. falciparum malaria positive patients attending the outpatient and inpatient department of RIMS Ranchi for a period of six months i.e. from January 2018 to June 2018, 100 participants were enrolled for the present study. 50 participants were P. falciparum malaria confirmed cases and 50 participants were without any clinical or laboratory evidence of malaria served as the control. Results: It revealed that the total cholesterol, HDL and LDL were significantly decreased -(P ≤0.05) while triglyceride and VLDL were not significantly changed in P. falciparum malaria patients (P ≥0.05). Conclusions: It can be concluded that alteration in lipid profile can be an index of severe malaria infection that may leads to poor prognosis, but specificity of malaria infection with lipid changes is questionable and need further studies.